UNUSUAL SOLUBILITY BEHAVIOR OF CYCLOSPORINE-A IN AQUEOUS-MEDIA - ISMAILOS, G; Reppas, C; Dressman, JB; Macheras, P. (JOURNAL OF PHARMACY AND PHARMACOLOGY, 1991)
The solubility of cyclosporin A was determined in water and in Sorensen buffers at pH 1.2 and 6.6 at temperatures ranging from 5 to 37-degrees-C. No differences in solubility behaviour were observed among the three aqeous media. Solubility was found to be inversely proportional to the temperature in each medium, indicating that the heat of solution was exothermic in each case.